How do you expand and simplify #(y+4)(y-3)+(y-2)(y-3)#?

2 Answers
Dec 11, 2016

Answer:

2(y+1)(y-3)

Explanation:

(y+4)(y-3)+(y-2)(y-3)
#y^2+y-12+y^2-5y+6#
#2y^2-4y-6#
#2(y+1)(y-3)#

Dec 11, 2016

Answer:

#2y^2-4y-6# or #y^2-2y-3#

Explanation:

FOIL: First-Outside-Inside-Last

  • left half
    #(y+4)(y-3)=y(y)+y(-3)+4(y)+4(-3)#
    #=y^2-3y+4y-12#
    #=y^2+y-12#
  • right half
    #(y-2)(y-3)=y(y)+y(-3)+(-2)y+(-2)(-3)#
    #=y^2-3y-2y+6#
    #=y^2-5y+6#

  • combine these #\rArr(y^2+y-12)+(y^2-5y+6)#
    simplify #2y^2-4y-6#
    or #y^2-2y-3# if you want to factor out a 2